2002
DOI: 10.1152/ajpcell.00409.2001
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of NBC4: a new electrogenic sodium-bicarbonate cotransporter

Abstract: Sodium-bicarbonate cotransporters are homologous membrane proteins mediating the electrogenic or electroneutral transport of sodium and bicarbonate. Of the functionally characterized sodium-bicarbonate cotransporters (NBC), NBC1proteins are known to be electrogenic. Here we report the cloning and functional characterization of NBC4c, a new splice variant of the NBC4 gene. At the amino acid level, NBC4c is 56% identical to NBC1 protein variants and 40% identical to electroneutral NBC3. When expressed in mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
3
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 35 publications
2
90
3
1
Order By: Relevance
“…Chloride was measured because other family members of SLC4A5 are involved with chloride-dependent cotransport, although SLC4A5 acts in a chloride-independent manner. 11 If complete counterregulation of a NaHCO 3 transport defect does not occur through other systems, these plasma measurements may be altered. However, extracellular acid-base balance is important to maintain, minimizing the probability that significant alterations would be found in plasma Na or CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Chloride was measured because other family members of SLC4A5 are involved with chloride-dependent cotransport, although SLC4A5 acts in a chloride-independent manner. 11 If complete counterregulation of a NaHCO 3 transport defect does not occur through other systems, these plasma measurements may be altered. However, extracellular acid-base balance is important to maintain, minimizing the probability that significant alterations would be found in plasma Na or CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the six NBCe2 splice variants reported (Pushkin et al, 2000b;Sassani et al, 2002;Xu et al, 2003), only NBCe2a-d sequences are confirmed by the human genome database and of these four transcripts only NBCe2a and NBCe2c (see Fig. 4) include a full complement of TM segments.…”
Section: Nbce2 Variantsmentioning
confidence: 91%
“…NBCe1 also operates with a 1:2 stoichiometry when heterologously expressed in Xenopus oocytes (Heyer et al, 1999;Sciortino and Romero, 1999) and human embryonic kidney cells (Shao et al, 2008). This mechanistic flexibility (reviewed by Gross and Kurtz, 2002) is reported to be controlled by changes in [Ca 2+ ] (Muller-Berger et al, 2001) and may involve phosphorylation of the transporter (Gross et al, 2001b). Defective functional expression of NBCe1 is linked to proximal renal tubular acidosis (pRTA) (Igarashi et al, 1999), which can be associated with growth and mental retardation as well as ocular and dental defects (e.g.…”
Section: Nbce1 Molecular Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the heart exist at least two electrogenic isoforms, called NBCe1 (also named NBC1) and NBCe2 (also named NBC4) which are encoded by the SLC4A4 gene [26], and the SLC4A5 gene [27], respectively, and one electroneutral isoform, named NBCn1 (also named NBC3), that is encoded by the SLC4A7 gene [28]. …”
Section: Electroneutral (Nnbc) and Electrogenic (Enbc) Isoforms Of Nbmentioning
confidence: 99%